2014
DOI: 10.1002/chem.201404795
|View full text |Cite
|
Sign up to set email alerts
|

Environment‐Sensitive Probes Containing a 2,6‐Diethynylpyridine Motif for Fluorescence Turn‐On Detection and Induction of Nanoarchitectures of Human Telomeric Quadruplex

Abstract: Bis(phenylethynyl)pyridylcarboxamides with amide side chains at the para position of the NH2 group possess strong solvatochromic properties compared with the meta analogues. Fluorescence binding titrations show that these probes exhibit remarkable fluorescence turn‐on responses upon interacting with the human telomeric G‐quadruplex (h‐TELO). Förster resonance energy transfer melting analysis shows the high selectivity of these probes for h‐TELO over duplex DNA. Isothermal titration calorimetry, as well as UV/V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…We observed that the emission maximum of BTC f is blue-shifted from 522 to 410 nm and the fluorescence intensity is simultaneously enhanced as the solvent polarity decreases from water to ethylacetate. These observations suggest that the enhancement in the fluorescence intensity along with the blue-shift in the emission spectra of the BTC f with the quadruplexes is a consequence of the proximity of BTC f to the non-polar hydrophobic regions 35 of the G-quadruplexes thereby manifesting the high affinity of BTC f towards the G-quadruplex structures.…”
Section: Resultsmentioning
confidence: 88%
“…We observed that the emission maximum of BTC f is blue-shifted from 522 to 410 nm and the fluorescence intensity is simultaneously enhanced as the solvent polarity decreases from water to ethylacetate. These observations suggest that the enhancement in the fluorescence intensity along with the blue-shift in the emission spectra of the BTC f with the quadruplexes is a consequence of the proximity of BTC f to the non-polar hydrophobic regions 35 of the G-quadruplexes thereby manifesting the high affinity of BTC f towards the G-quadruplex structures.…”
Section: Resultsmentioning
confidence: 88%
“…83 BPEP 1 is a bis(phenyethynyl)pyridylcarboxamide compound. 84 CV refers to Crystal violet; ThT to Thioflavin T. c ex -NDI is an extended naphthalene diimide derivative specific for parallel G-quadruplexes. 81 Hemin is a natural G-quadruplex ligand found in DNAzymes (see section 6.3).…”
Section: Ligandsmentioning
confidence: 99%
“…Spectroscopic data suggest an intercalative mechanism of cationic porphyrin binding to potassium-free G-wires; such a binding mode, expectedly, is absent when dealing with the potassium form of this G-wire. 135 Das et al 84 have reported interesting data showing that certain end-stacking bis(phenyethynyl)pyridylcarboxamide (BPEP) ligands assist the formation of G-wires by mixed-topology intramolecular G4 units formed by the human/vertebrate telomeric repeat (T 2 AG 3 ) 4 (h-TELO). The authors hypothesized that these ligands end-stack at either end of individual intramolecular h-TELO quadruplex units and help to join together such individual units to generate long wires.…”
Section: G4 Ligands Binding To G-wiresmentioning
confidence: 99%
See 1 more Smart Citation
“…6d–i). Fluorescence binding titration revealed that these carbazole derivatives are environmentally sensitive probes for the G-quadruplex3640. The major lead compound Tz 1 exhibited a selective fluorescence enhancement (3.7-fold) upon binding with G-quadruplex with a 33 nm blueshift, whereas it barely showed any enhancement upon titration with duplex DNA.…”
Section: Resultsmentioning
confidence: 99%